The Jewish Past of Eastern Europe - Lilla Etelka Dohi Trepszker (CES Working Papers, 2015)
In Transylvania, buildings with a high quality architecture have been constructed along the centuries. The purpose of the present study is to document the built heritage of Transylvania, particularly the Jewish buildings and especially those that had been neglected over the last years. The article is the continuation of the article about the Jewish architecture in Transylvania, with a case study about the Jewish girls' school in Satu Mare. The research domain is interdisciplinary because it links History, Architecture, Art history and the problem of Globalization as well. The niche in this domain remains the fact that the buildings are not identified, rehabilitated, or promoted. Previous studies have mostly focused on synagogues and prayer houses. Most of the other precious buildings have been left aside. This study offers a new approach to change the point of view of the people who live in Romania, and helps them appreciate the heritage they have received.
Keywords: O18; O34; R14; R21; 330; Jewish building; heritage of Transylvania; transnational dialogue; identity; globalisation problems